A Metallosupramolecular Octahedron Assembled from Twelve Copper(I) Metal Ions and Six 4, 4′‐(1, 2‐Phenylene)bis(3, 5‐dimethylpyrazol‐1‐ide) Ligands1. Issue 8 (15th May 2013) - Grzywa, Maciej; Bredenkötter, Björn; Denysenko, Dmytro; Spirkl, Sebastian; Nitek, Wojciech; Volkmer, Dirk
Abstract The novel coordination compound [CuI12(C16H16N4)6]·8DMAc, (2), (DMAc = N, N‐dimethylacetamide) was prepared in solvothermal or microwave assisted reaction. It contains four metallamacrocyclic trinuclear copper(I) pyrazolate coordination units, which occupy four (opposite) faces of an imaginary metallosupramolecular octahedron. Six (4, 4′‐(1, 2‐phenylene)bis(3, 5‐dimethylpyrazol‐1‐ide) ligands (L12–) are placed at the corners of the octahedron. Crystals of the free ligand H2L1 [1, 2‐bis(3, 5‐dimethyl‐1H‐pyrazol‐4‐yl)benzene, (1)], and [CuI12(C16H16N4)6]·8DMAc (2), were characterized by single‐crystal X‐ray structure analyses. Lingand 1 crystallizes in the monoclinic crystal system, with: a = 9.0118(9), b = 14.0075(11), c = 11.7484(11) Å, β = 104.945(5)°, V = 1432.9(2) Å3, space group P21/c (no. 14). Compound 2 crystallizes in the tetragonal system, with: a = b = 19.506(5), c = 42.888(5) Å, V = 16318(6) Å3, space group I41/amd (no. 141). Compound 2 represents a porous structure, where each metallosupramolecular octahedron encloses a solvent‐filled cavity of 889 Å3 (accounting for 6 DMAc molecules, 21.8 % of the cell volume). The incomplete crystal packing arrangement of adjacent [CuI12(C16H16N4)6] moieties in addition leads to solvent‐filled interstitial voids accounting to 8.1 % of the cell volume. Removing solvent molecules in vacuo is accompanied by reversible structural changes, leading to a partial loss of porosity, as revealed by Ar‐BET sorption analysis. Compounds 1 and 2 were further characterized by elemental and thermogravimetric analysis, X‐ray powder diffraction, FTIR‐, UV/Vis‐ and fluorescence spectroscopy. Preliminary results on the activation of molecular oxygen by compound 2 are presented.